2022
DOI: 10.3389/fimmu.2022.1022677
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of long noncoding RNA HCP5/miR-216a-5p/ZEB1 axis inhibits the malignant biological function of laryngeal squamous cell carcinoma cells

Abstract: Previous studies find that long noncoding RNA human leukocyte antigen complex P5 (HCP5) is regarded as an oncogene via accelerating cancer cell growth, invasion, metastasis, vascularization, and drug resistance in renal cell carcinoma, gastric cancer, and colorectal cancer. Nevertheless, the effect and regulatory mechanism of HCP5 in laryngeal squamous cell carcinoma (LSCC) remains unknown. In this study, HCP5 expression levels were confirmed to be prominently raised in LSCC cell lines. HCP5 knockdown reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Researchers have confirmed that lncRNAs serve as promising biomarkers and therapeutic targets for LSCC (Lv et al, 2022). For instance, the downregulation of lncRNA HCP5/miR-216a-5p/ZEB1 axis has been shown to inhibit the malignant behavior of LSCC cells (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…Researchers have confirmed that lncRNAs serve as promising biomarkers and therapeutic targets for LSCC (Lv et al, 2022). For instance, the downregulation of lncRNA HCP5/miR-216a-5p/ZEB1 axis has been shown to inhibit the malignant behavior of LSCC cells (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…LncRNAs can act as sponges to interact with miRNAs, and also have an effect on their production and degradation, eventually leading to the alteration of target genes [ 18 ]. In addition, both lncRNAs and miRNAs are known to be involved in cell proliferation, apoptosis, metastasis, and tumor microenvironment (TME) [ 19 , 20 ]. Therefore, regulation of aberrant lncRNAs and miRNAs may alleviate the initiation and development of various tumors.…”
Section: Introductionmentioning
confidence: 99%